2020
DOI: 10.3389/fpsyg.2020.600739
|View full text |Cite
|
Sign up to set email alerts
|

Novelty Seeking and Mental Health in Chinese University Students Before, During, and After the COVID-19 Pandemic Lockdown: A Longitudinal Study

Abstract: COVID-19 has created significant concern surrounding the impact of pandemic lockdown on mental health. While the pandemic lockdown can be distressing, times of crisis can also provide people with the opportunity to think divergently and explore different activities. Novelty seeking, where individuals explore novel and unfamiliarly stimuli and environments, may enhance the creativity of individuals to solve problems in a way that allows them to adjust their emotional responses to stressful situations. This stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
84
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(90 citation statements)
references
References 80 publications
(133 reference statements)
4
84
1
1
Order By: Relevance
“…Similarly, overall symptom predominance decreased following measures lifting [ 24 ]. Conversely, symptoms of stress, anxiety, and depression in a study of Chinese students decreased during national lockdown, and subsequently increased after measures were removed [ 23 ]. Minimal changes to psychological well-being were described by Zhou et al six weeks after national lockdown ended in China [ 58 ].…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, overall symptom predominance decreased following measures lifting [ 24 ]. Conversely, symptoms of stress, anxiety, and depression in a study of Chinese students decreased during national lockdown, and subsequently increased after measures were removed [ 23 ]. Minimal changes to psychological well-being were described by Zhou et al six weeks after national lockdown ended in China [ 58 ].…”
Section: Resultsmentioning
confidence: 99%
“…The COVID-19 pandemic has intensified people's awareness of death and death-related anxiety (Li et al, 2020c). The theoretical underpinnings of terror management theory (TMT) and the meaning maintenance model (MMM) consider the impact of death-related anxiety and reach similar conclusions regarding the importance of culturally salient relationship models.…”
Section: Introduction Backgroundmentioning
confidence: 99%
“…This notion is evident in contemporary Chinese culture. For example, Li et al (2020c) maintains that China being a "dear mother" is a common motif in contemporary Chinese popular culture (e.g., music and literature), representing the cultural belief that the state is a symbolic parental figure for Chinese people, and reinforcing the cultural expectation of being filial to authority.…”
Section: Introduction Backgroundmentioning
confidence: 99%
“…Many countries applied (and still apply) similar measures to limit the spread of the virus. These constraints imply a restriction of movement, the need to adapt working methods (remote working, partial unemployment), a modification of daily life within households (e.g., management of children, protection of vulnerable people, living conditions), and a decreased wellbeing (linked to health issues, restrictions of activities and social interactions, or economic consequences) with elements of distress, loneliness, and anxiety [1][2][3][4][5] . Paradoxically, during this period, general and social media have reported that individuals and businesses seemed to show great adaptability to face the situation by finding innovative solutions as well as creative behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…The situation related to COVID-19 likely has a major impact on many if not all the creativity dimensions or factors described above, by affecting our emotions, motivations, and wellbeing, modifying our environment, our lifestyle, and availability, but also by modifying the standards and incentives of our society during this period, opening a new framework of thought 30,31 . Several studies reported how the pandemic and lockdown had increased psychological distress, mood disorders, loneliness, and anxiety [1][2][3][4][5] , with a potential negative impact on creativity. Nevertheless, the few existing scientific studies that explored creativity during the COVID-19 pandemic have indeed suggested that the lockdown period facilitated everyday creativity 32,33 or that creative abilities could help people dealing with the situation and improve their wellbeing 3,34,35 .…”
Section: Introductionmentioning
confidence: 99%